Inspiratory muscle training fails to improve endurance capacity in athletes - Williams, J. S.; Wongsathikun, J.; Boon, S. M.; Acevedo, E. O. (Medicine & Science in Sports & Exercise, 2002)
The purpose of this study was to examine the effects of specific inspiratory muscle training (IMT) on respiratory muscle strength and endurance and whole-body endurance exercise capacity in competitive endurance athletes. METHODS: Seven collegiate distance runners (5 male/2 female; VO2max = 59.9 +/- 11.7 mL.kg-1.min-1) were recruited to participate in this study. Initial testing included maximal oxygen consumption (VO2max), sustained maximal inspiratory mouth pressure (MIP), breathing endurance time (BET) at 60% MIP, and endurance run time (ERT) at 85% VO2max. Heart rate (HR), minute ventilation (VE), oxygen consumption (VO2), and ratings of perceived dyspnea (RPD) were recorded at 5-min intervals and during the last minute of the endurance run. Blood lactate concentration (BLC) was also obtained immediately before and at 2 min after the endurance run. All testing was repeated after 4 wk of IMT (50-65% MIP, approximately 25 min.d-1, 4-5 sessions/week, 4 wk). RESULTS: After 4 wk of IMT, MIP and BET were significantly increased compared with pretraining values (P < 0.05). No significant differences between pre and post values were observed in VO2max or ERT at 85% VO2max after IMT. No significant differences between pre and post values were detected in HR, VE, VO2, or RPD during the endurance run as measured at steady state and end of the test after IMT. BLC was not significantly different before or at 2 min after the endurance run between pre and post IMT. CONCLUSION: These results suggest that IMT significantly improves respiratory muscle strength and endurance. However, these improvements in respiratory muscle function are not transferable to VO2max or endurance exercise capacity as assessed at 85% VO2max in competitive athletes.